Qualitative data analysis - Grbich, Carol (London ; Thousand Oaks, Calif. : SAGE Publications, 2013)
"In this fully updated and expanded Second Edition, Carol Grbich provides a guide through current issues in the analysis of qualitative data. Packed with detailed examples, a glossary, further reading lists and a section on writing up, this easy to read text is exactly what you need to get you started in qualitative research."--Publisher's website.
Part 1: General approaches to collecting and analyzing qualitative data. Introduction ; Design Methodologies, Data Management and Analytical Approaches ; Incorporating Data from Multiple Sources: Mixing Methods. -- Part 2 :Traditional analytical approaches. Classical Ethnography ; Critical Ethnographic Approaches ; Feminist Approaches ; Grounded Theory ; Phenomenology. -- Part 3: Newer qualitative approaches. Postmodern Influences on Society and Qualitative Research ; Auto-Ethnography ; Poetic Inquiry ; Ethnodrama and Performative Art ; Cyber-Ethnography and E-Research. -- Part 4: Analytic approaches for existing documentation. Structuralism and Post-Structuralism Semiotic Structural and Post-Structural Analysis (Deconstruction) ; Content Analysis of Texts ; Content Analysis of Visual Documentation ; Narrative Analysis ; Conversation Analysis ; Discourse Analysis. -- Part 5: Data management using qualitative computer programmes. Coding ; An Overview of Qualitative Computer Programs. -- Part 6: Interpreting and presenting qualitative data. Theorizing from Data ; Innovative Data Display.
Previous ed.: 2007.
Keywords: Social sciences; Qualitative research